Unravelling the nanostructure of strawberry fruit pectins by endo-polygalacturonase digestion and atomic force microscopy. (1st June 2017) - Paniagua, Candelas; Kirby, Andrew R.; Gunning, A. Patrick; Morris, Victor J.; Matas, Antonio J.; Quesada, Miguel A.; Mercado, José A.
Highlights: Strawberry fruit pectins are visualized by AFM as linear chains and large complexes. Digestion with fungal endoPG reduces the size of linear chains and complexes. An acid treatment to eliminate RGII dimers diminishes the number of complexes. Pectin chains are formed by a mixture of HG and HG linked to an endoPG resistant unit. RGII dimers are involved in the formation of the pectin complexes. Abstract: Pectins analysed by AFM are visualized as individual chains, branched or unbranched, and aggregates. To investigate the nature of these structures, sodium carbonate soluble pectins from strawberry fruits were digested with endo-polygalacturonase M2 from Aspergillus aculeatus and visualized by AFM. A gradual decrease in the length of chains was observed as result of the treatment, reaching a minimum LN value of 22 nm. The branches were not visible after 2 h of enzymatic incubation. The size of complexes also diminished significantly with the enzymatic digestion. A treatment to hydrolyse rhamnogalacturonan II borate diester bonds neither affected chains length or branching nor complex size but reduced the density of aggregates. These results suggest that chains are formed by a mixture of homogalacturonan and more complex molecules composed by a homogalacturonan unit linked to an endo-PG resistant unit. Homogalacturonan is a structural component of the complexes and rhamnogalacturonan II could be involved in their formation.